2011
DOI: 10.2147/opth.s16172
|View full text |Cite
|
Sign up to set email alerts
|

Advanced retinoblastoma treatment: targeting hypoxia by inhibition of the mammalian target of rapamycin (mTOR) in LHBETATAG retinal tumors

Abstract: Purpose:The purpose of this study is to analyze the dose response of the mammalian target of rapamycin (mTOR) inhibitor, rapamycin, on tumor burden and hypoxia, and study the treatment effect on vasculature in LHBETATAG retinal tumors.Methods:This study was approved by the Institutional Animal Care and Use Committee and follows Association for Research in Vision and Ophthalmology guidelines. Eighteen-week-old LHBETATAG retinal tumor eyes (n = 30) were evaluated. Mice were divided into five groups and received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The authors found that 90% and 100% DMSO worsened ocular inflammation, while doses lower than 30% demonstrated anti-inflammatory properties [ 30 ]. Other studies conducted in 2010 and 2011 saw its administration both subconjunctivally and following trabeculotomy [ 31 , 32 ]. A synopsis of published DMSO ocular findings is detailed in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that 90% and 100% DMSO worsened ocular inflammation, while doses lower than 30% demonstrated anti-inflammatory properties [ 30 ]. Other studies conducted in 2010 and 2011 saw its administration both subconjunctivally and following trabeculotomy [ 31 , 32 ]. A synopsis of published DMSO ocular findings is detailed in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin is a chemotherapy agent used in the treatment of RB [28,29]. This study aimed to investigate the effects of overexpression of the BGN gene in WERI-Rb-1 human RB cells including the response to rapamycin.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is of particular interest, as a recent report showed that the PI3K/Akt/mTOR pathway was dysregulated in human RB [8]. As an inhibitor of mTOR, rapamycin has particular cytotoxic effects on hypoxic cell populations [28,29]. The findings of the present study also showed that inhibition of the PI3K/Akt/mTOR pathway suppressed the activation of NF-κB signaling by increasing the cytoplasmic of IκBα and reducing cell nuclear expression levels of p65.…”
Section: Discussionmentioning
confidence: 99%
“…A combination therapy that targets both pericytes and angiogenesis has been shown to cause a higher percentage of tumor burden and vasculature decrease 53. Also, the low O 2 -sensitive mTOR that stimulates cellular metabolism and angiogenesis through the upregulation of HIF26 was found to decrease tumor burden by both decreasing intratumoral hypoxia and mature blood vessels 55…”
Section: Discussionmentioning
confidence: 99%
“… 53 Also, the low O 2 -sensitive mTOR that stimulates cellular metabolism and angiogenesis through the upregulation of HIF 26 was found to decrease tumor burden by both decreasing intratumoral hypoxia and mature blood vessels. 55 …”
Section: Discussionmentioning
confidence: 99%